A Comparative Analysis of Social Impact Bond and Conventional Financing Approaches to Health Service Commissioning in England: The Case of Social Prescribing. Issue 2 (3rd March 2020) - Dayson, Chris; Fraser, Alec; Lowe, Toby
Abstract: The article compares two social prescribing interventions in Northern England. One was financed through a Social Impact Bond (SIB) and the other was financed in a more conventional way. It utilises a comparative approach to understand the extent to which different methods of financing social prescribing conform to key features of the New Public Management (NPM) or New Public Governance (NPG) in their design and implementation. It finds that a SIB approach tends towards NPM during programme design and implementation and that this creates challenges for social prescribing programmes, the complexity of which appear better suited to an NPG-based relational approach.